Screening of Active Components and Key Targets of Radix Codonopsis in the Treatment of Gastric Cancer - Lijun Tang; Jinhui Chen; Jin Yin; Mingli Fang (Journal of Chemistry)
Gastric cancer is the fifth most common cancer type in the world. The incidence and mortality of gastric cancer in China ranks second among malignant tumors in the country. At present, the main treatment method of gastric cancer is still surgical resection combined with chemotherapy. However, chemotherapy drugs will cause serious toxic and side effects on other normal tissues and cells. At the same time, chemotherapy drugs can make patients develop drug resistance and seriously affect the curative effect. By contrast, Chinese medicine has more advantages in the treatment of cancer. Dangshen (Radix Codonopsis), a traditional Chinese medicine, has been proved to be effective for the clinical treatment of gastric cancer. However, due to the complex components of Dangshen, the main active components and pharmacological mechanism for its treatment of gastric cancer are still unclear. In this study, the main active components and pharmacological mechanism of Radix Codonopsis in the treatment of gastric cancer were preliminarily explored based on network pharmacology and molecular docking. We obtained bioactive compounds and targets from Radix Codonopsis from the Chinese Medicine System Pharmacology Database (TCMSP) and constructed the active ingredient-target network of Codonopsis pilosula. We then obtained targets related to gastric cancer from the disease database. The common targets of Radix Codonopsis and gastric cancer were the key target of Radix Codonopsis for the treatment of gastric cancer. Then, we used Metascapedatabase to conduct functional enrichment analysis on the key targets of Radix Codonopsis for the treatment of gastric cancer to clarify the mechanism of Radix Codonopsis for the treatment of gastric cancer. We constructed a network to screen the main bioactive compounds and therapeutic targets, assessed the prognostic value of the main target genes by survival analysis, and finally assessed the binding affinity of the main target genes and main bioactive compounds of Radix Codonopsis for the treatment of gastric cancer by molecular docking. The results showed that the main active compounds of Codonopsis pilosula in treating gastric cancer were luteolin and cryptotanshinone, which played a role in the treatment of gastric cancer through the multitarget and multipathway mechanism.